2005
DOI: 10.1016/j.ajog.2004.09.021
|View full text |Cite
|
Sign up to set email alerts
|

The Preterm Prediction study: Association between maternal body mass index and spontaneous and indicated preterm birth

Abstract: Obesity before pregnancy is associated with a lower rate of spontaneous preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
208
4
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(234 citation statements)
references
References 26 publications
17
208
4
5
Order By: Relevance
“…The need for induction of labour and caesarean deliveries when the mother is obese or morbidly obese has been reported by numerous studies. 5,[11][12][13][14][15][16][17][18][19] Vahratian et al 20 discuss the need for more frequent administration of oxytocin to stimulate contractions during labour and a significant increase in emergency caesarean deliveries in the obese mother. Rode et al 21 also address a significant increase in emergency caesarean delivery rates, as well as overall caesarean rates, and elective caesareans.…”
Section: Discussionmentioning
confidence: 99%
“…The need for induction of labour and caesarean deliveries when the mother is obese or morbidly obese has been reported by numerous studies. 5,[11][12][13][14][15][16][17][18][19] Vahratian et al 20 discuss the need for more frequent administration of oxytocin to stimulate contractions during labour and a significant increase in emergency caesarean deliveries in the obese mother. Rode et al 21 also address a significant increase in emergency caesarean delivery rates, as well as overall caesarean rates, and elective caesareans.…”
Section: Discussionmentioning
confidence: 99%
“…In LMICs, IUGR and preterm delivery share several common determinants such as low body mass index, malaria, smoking, pregnancy-induced hypertension, and pre-eclampsia. 25,29,51,65 Thus, countries with high prevalence of risk factors (such as low maternal body mass index and malaria) with a resulting high prevalence of term LBW are also more likely to present high rates of preterm LBW births. In addition, a number of studies 7,23,28,45,50 show that preterm births are more frequent among poor populations.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that obesity is protective against spontaneous preterm birth, 4,5 though there may be a specific relationship between obesity and early preterm premature rupture of membranes. 7 However, no studies have examined outcomes in the obese patient with CI and cerclage placement.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Past studies have demonstrated that obesity is protective against spontaneous preterm delivery. 4,5 However, it has been shown to be a significant risk factor for indicated preterm delivery. [5][6][7] Recent data indicate that preterm premature rupture of membranes is significantly increased in women with a body mass index (BMI) >30 kg m À2 .…”
Section: Introductionmentioning
confidence: 99%